The Effect of Aging on the Cracking Resistance of Recycled Asphalt - Mojtaba Mohammadafzali; Hesham Ali; James A. Musselman; Gregory A. Sholar; Aidin Massahi (Advances in Civil Engineering)
Fatigue cracking is an important concern when a high percentage of Reclaimed Asphalt Pavement (RAP) is used in an asphalt mixture. The aging of the asphalt binder reduces its ductility and makes the pavement more susceptible to cracking. Rejuvenators are often added to high-RAP mixtures to enhance their performance. The aging of a rejuvenated binder is different from virgin asphalt. Therefore, the effect of aging on a recycled asphalt mixture can be different from its effect on a new one. This study evaluated the cracking resistance of 100% recycled asphalt binders and mixtures and investigated the effect of aging on this performance parameter. The cracking resistance of the binder samples was tested by a Bending Beam Rheometer. An accelerated pavement weathering system was used to age the asphalt mixtures and their cracking resistance was evaluated by the Texas Overlay Test. The results from binder and mixture tests mutually indicated that rejuvenated asphalt has a significantly better cracking resistance than virgin asphalt. Rejuvenated mixtures generally aged more rapidly, and the rate of aging was different for different rejuvenators.